2019
DOI: 10.1136/bmjopen-2018-027122
|View full text |Cite
|
Sign up to set email alerts
|

Towards a safer culture: implementing multidisciplinary simulation-based team training in New Zealand operating theatres - a framework analysis

Abstract: AimNetworkZ is a simulation-based multidisciplinary team-training programme designed to enhance patient safety by improving communication and teamwork in operating theatres (OTs). In partnership with the Accident Compensation Corporation, its implementation across New Zealand (NZ) began in 2017. Our aim was to explore the experiences of staff – including the challenges they faced – in implementing NetworkZ in NZ hospitals, so that we could improve the processes necessary for subsequent implementation.MethodWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…With respect to context, we will now address the countries where the interventions were carried out and the specific settings in which the IPE strategies were implemented. Regarding the countries, we found that all studies were conducted in countries belonging to the Global North, such as the United States (Carney et al, 2019;Dematteo & Reeves, 2011;Gros et al, 2021;Lee et al, 2021;Marrone, 2018;Nagelkerk et al, 2014;Rider et al, 2019;Roberts et al, 2014;Wong et al, 2016), Canada (Bajnok et al, 2012;Christofilos et al, 2015;Villemure et al, 2019), Australia (Braithwaite et al, 2013;Brewer & Flavell, 2020), New Zealand (Jowsey et al, 2019;Pullon & Fry, 2005), United Kingdom (Hinde et al, 2016;Slater et al, 2012), Germany (Tahtali et al, 2017), Sweden (Meurling et al, 2013) and Switzerland (Kolbe et al, 2013). The clinical settings were heterogeneous, with a predominance (Christofilos et al, 2015;Dematteo & Reeves, 2011;Gros et al, 2021;Kolbe et al, 2013;Marrone, 2018;Meurling et al, 2013;Roberts et al, 2014;Villemure et al, 2019;Wong et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…With respect to context, we will now address the countries where the interventions were carried out and the specific settings in which the IPE strategies were implemented. Regarding the countries, we found that all studies were conducted in countries belonging to the Global North, such as the United States (Carney et al, 2019;Dematteo & Reeves, 2011;Gros et al, 2021;Lee et al, 2021;Marrone, 2018;Nagelkerk et al, 2014;Rider et al, 2019;Roberts et al, 2014;Wong et al, 2016), Canada (Bajnok et al, 2012;Christofilos et al, 2015;Villemure et al, 2019), Australia (Braithwaite et al, 2013;Brewer & Flavell, 2020), New Zealand (Jowsey et al, 2019;Pullon & Fry, 2005), United Kingdom (Hinde et al, 2016;Slater et al, 2012), Germany (Tahtali et al, 2017), Sweden (Meurling et al, 2013) and Switzerland (Kolbe et al, 2013). The clinical settings were heterogeneous, with a predominance (Christofilos et al, 2015;Dematteo & Reeves, 2011;Gros et al, 2021;Kolbe et al, 2013;Marrone, 2018;Meurling et al, 2013;Roberts et al, 2014;Villemure et al, 2019;Wong et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Significant methodological variability was observed in the papers. Specifically, five documents were found to have a qualitative approach (Brewer & Flavell, 2020;Christofilos et al, 2015;Dematteo & Reeves, 2011;Jowsey et al, 2019;Rider et al, 2019), among which there were two exploratory phenomenological papers (Brewer & Flavell, 2020;Jowsey et al, 2019), two based on grounded theory (Christofilos et al, 2015;Rider et al, 2019) and one case study (Dematteo & Reeves, 2011). In addition, there were six mixed-methods studies (Bajnok et al, 2012;Carney et al, 2019;Kolbe et al, 2013;Lee et al, 2021;Nagelkerk et al, 2014;Slater et al, 2012) and ten quantitative studies (Braithwaite et al, 2013;Gros et al, 2021;Hinde et al, 2016;Marrone, 2018;Meurling et al, 2013;Roberts et al, 2014;Tahtali et al, 2017;Villemure et al, 2019;Wong et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These 'ripple' effects reinforce the importance of interventions for senior staff about responding to concerns raised by team members. In multidisciplinary simulation-based team training, 30 where flattened hierarchies can be created during the debriefing discussions, senior clinical staff hear the views of others, and may be made more aware of their influence on the team and on subsequent patient care.…”
Section: The Influence Of Culturementioning
confidence: 99%
“…El teatro es una herramienta con la que cuentan distintos ámbitos para mejorar los procesos, la forma en la que podrían enfrentar las situaciones de su trabajo, mejorar la comunicación y el trabajo en equipo en ámbitos tan especializados como lo son los quirófanos de los hospitales, indicando que con esta práctica se mejora la cohesión del hospital, el entusiasmo e impulso del personal y la integración del equipo a los distintos programas (Jowsey et al, 2019;Robertson et al, 2015). Además, el uso del teatro para mejorar las competencias de los estudiantes de forma interdisciplinar para abordar distintos casos simulados, se indica como una adecuada estrategia para lograr impacto positivo en el aprendizaje de las competencias básicas interprofesionales (Wen et al, 2019).…”
Section: Introductionunclassified